Swedish Ecstasy : Hilma Af Klint, August Strindberg & other visionaries. - Birnbaum, Daniel (Brussels : Mercatorfonds & Bozar Books, 2023)
Birnbaum, Daniel ; Ödlund, Christine ; McNeilly, Stephen ; Brett, James ; Fer, Briony ; Cornell, Peter ; Voss, Julia ; Higgie, Jennifer ; Florin, Magnus ; Höller, Carsten ; Edefalk, Celia ; Tirén, Svante
Swedish Ecstasy: Hilma af Klint, August Strindberg and Other Visionaries, Bozar, Brussels, 17 february - 21 may 2023
boek
Keywords: Af Klint, Hilma; Cassel, Anna; Strindberg, August; Hill, Carl Frederik; Josephson, Ernst; Ödlund, Christine